Development of the Islamic financial services industry - С. Пралиева; В. Заболотникова; A. Асилова (Хабаршысы. Экономика сериясы, 2017)
The global financial crisis has increased interest to Islamic finance as a form of mediation, contributing for maintaining of a financial stability. This stability is demonstrated by institutions that offer Islamic financial services, providing insight into the viability of financing based on the Sharia rules. Islamic finance has made progress in Asia in recent years, yet there is still great potential for further growth. Everywhere there is evidence that Islamic finance expands its borders in Asia. This article discusses the development of Islamic banking in the world. The global market for financial services, the relevant provisions of the Qur’an and Sharia canons, over the past decade has increased almost 6 times - from 150 billion US dollars till 822 billion US dollars. At the same time according to some experts, this market has a seven-fold growth potential - up to 4 trillion US dollars. Up today, Islamic finance has developed in more than 50 countries, including 16 countries that amended the legislation in order to create optimal conditions for its further development. These include both Islamic countries and Europe. At the present stage, Islamic financial services market shows active development in the United States, Britain, France, Germany, Canada, China, Japan and other countries.